Serological surveillance for Tahyna virus (California encephalitis orthobunyavirus, Peribunyaviridae) neutralizing antibodies in wild ungulates in Austria, Hungary and Romania. (8th March 2018) - Camp, J. V.; Haider, R.; Porea, D.; Oslobanu, L. E.; Forgách, P.; Nowotny, N.
Summary: A serosurvey for Tahyna virus (TAHV), a mosquito‐borne California encephalitis orthobunyavirus ( Peribunyaviridae ) endemic to Europe, was performed to estimate the activity of TAHV on a broad geographic scale. Sera from wild boar ( Sus scrofa ), roe deer ( Capreolus capreolus ) and red deer ( Cervus elaphus ) were collected from Austria, Hungary and Romania. Samples were tested for neutralizing antibodies against TAHV using a virus microneutralization assay. The results demonstrate that TAHV transmission to mammals is widespread in Europe, particularly in the wild boar population where the mean rate of seroconversion is 15.2%.